Efeitos da formação do reservatório da PCH Ibirama sobre os atributos e estrutura da comunidade zooplanctônica - Fernandes, Cleomar (2013)
Due to the energy demand of the country, the small hydropower plants (SHPs) are seen as a great energy strategy, because of the low cost and rapidity of construction, however, these king of power plant have caused changes in the biological and hydrological system of the body of the river. This study was conducted at SHP Ibirama, Hercílio River, State of Santa Catarina, and had as tested hypotheses: a) the construction of a small hydroelectric power plant (SHP) changes the attributes and structure of zooplankton community, b) the reservoir of SHP Ibirama, will positively affect zooplankton community downstream of the dam, c) the physical and chemical variables of the water influence the abundance of zooplankton community. To test these hypotheses were evaluated the attributes (richness, diversity and evenness) and structure (abundance) of the zooplankton community in the area of influence of SHP Ibirama, on the Hercílio River, before and after the formation of the reservoir, and the correlation was performed between some physical and chemical variables and the abundance of zooplankton community. The zooplankton and water sampling were carried out in 8 collections, being 4 before the impoundment and 4 after, at four points (grouped as Reservoir and downstream), to collect zooplankton 600 liters of water was filtered per sample. The zooplankton community was represented by 61 taxa, 42 rotifers, 15 cladocerans and 4 copepods. The rotifers showed tendency to reduce the abundance with the increase of the pH of water, however, the abundance of cladocerans increased, and the abundance of copepods showed great correlation with increase in temperature of water, phosphorus, ammoniacal nitrogen and nitrate, and less with increased turbidity and electric conductivity. It was observed, in general that the impoundment of the Hercílio River to formation the reservoir of SHP Ibirama, changed the attributes and structure of the zooplankton community, being proved through the analysis of attributes, where richness was higher after the impoundment, mainly of rotifers and Cladocerans in both, the reservoir and downstream of the dam, however the abundance of the groups was lower after impoundment. We also observed significant variation in the values of species diversity, mainly related to the results of dominance. The evenness also varied after impoundment, indicating the predominance of some species in terms of abundance. Thus, the first hypothesis was confirmed by the changes of the attributes and structure of zooplankton community after impoundment. The second hypothesis was partially rejected, since only the rotifers were positively affected downstream of the dam in terms of richness after the impoundment, and finally, the third hypothesis was confirmed by the strong correlation between the physical and chemical variables and abundance of zooplankton community. Thus, there is a need to evaluate the changes in the physical and chemical variables of the water, and the attributes and structure of zooplankton community structure in other reservoirs, in view of the lack of information about the possible changes in the community resulting from impoundments, and is important to investigate which environmental factors are responsible for these changes, so it is possible to predict and mitigate negative impacts on aquatic biota.